The Company's Mentoring Program In Supporting Staff Development - Akh Jalal; Mochammad Isa Anshori (Universitas Veteran Bangun Nusantara, 2023)
This research aims to analyze the role of mentoring programs in supporting staff development within a company. Mentoring programs are an effective method of providing guidance and support to staff members, enabling them to reach their full potential and develop job-relevant skills. The research employs a library research approach, collecting data from relevant theoretical sources and empirical studies. Through the analysis, this research reveals that mentoring programs play a significant role in staff development in terms of improving the quality of human resources, enhancing staff productivity, increasing employee and organizational performance, and creating job satisfaction and a positive work environment. Thus, mentoring programs contribute to the overall development of the organization and foster a staff development culture that supports the company's goals.